Design, Synthesis, In Vitro Biological Activity Evaluation and Stabilized Nanostructured Lipid Carrier Formulation of Newly Synthesized Schiff Bases-Based TMP Moieties - Syed Nasir Abbas Bukhari; Mohamed Y. Zakaria; Muhammad Usman Munir; Naveed Ahmad; Mervat A Elsherif; Rasha Emad Badr; Ahmad Khalaf Hassan; Ali H. Abu Almaaty; Islam Zaki (Pharmaceuticals, 2022)
A series of novel Schiff bases-based TMP moieties have been designed and synthesized as potential anticancer agents. The target Schiff bases were screened for their cytotoxic activity against the MDA-MB-231 breast cancer cell line. Most of the tested molecules revealed good cytotoxic activity, especially compounds 4h, 4j and 5d. Being the most potent, compound 4h showed good tubulin polymerization inhibition activity as revealed by immunofluorescence analysis and ELISA assay. Additionally, compound 4h was screened for cell cycle disturbance and apoptosis induction. Pre-G1 apoptosis and cell growth halt at the G2/M phase were discovered to be caused by it. Moreover, compound 4h induced apoptosis via p53 and Bax activation, as well as reduced the level of Bcl-2. Additionally, the most potent compound 4h was lodged on nanostructured lipid carriers (NLCs). 23 full factorial design was involved to govern the influence of the fabrication variables on the in vitro characters of the casted NLCs. F3 was picked as the optimum formula exhibiting dominant desirability value 0.805, EE% 95.6 ± 2.4, PS 222.4 ±18.7, PDI 0.23 ± 0.05 and ZP −39.2 ± 3.9 Mv. Furthermore, F3 affirmed improved solubility and release over the drug suspension. In the comparative cytotoxic activity, F3 was capable of diminishing the IC50 by around 2.15 times for pure 4h, while nearly close to the IC50 of the reference drug. Thus, NLCs could be a potential platform for boosted antitumor activity.